Frequency of Iron Deficiency Anemia among Children Presenting with Breath Holding Spells - Rehman, Sana; Masood, Tahir; Arshad, Arslan (Biological and Clinical Sciences Research Journal, 2025)
Breath-holding spells (BHS) in young children, triggered by emotions or trauma, are benign but concerning for parents. Iron deficiency anemia (IDA) may contribute to BHS, making this association important, particularly in regions such as Pakistan, where nutritional anemia is common. Objective: To determine the frequency of iron deficiency anemia among children presenting with breath-holding spells at a tertiary care hospital. Methods: A cross-sectional study was conducted in the Department of Paediatrics at Arif Memorial Teaching Hospital, Lahore, from 5th June to 5th November 2025. A total of 141 children aged 6–60 months presenting with breath-holding spells were enrolled using non-probability consecutive sampling. Children with congenital heart disease, epilepsy, severe malnutrition, hemoglobin levels below 5 g/dl, or those receiving anticonvulsant therapy were excluded to minimize confounding factors. Demographic and clinical data were recorded, and venous blood samples were collected for complete blood count and serum ferritin estimation. Iron deficiency anemia was diagnosed using predefined hematological and biochemical criteria. Data were analyzed using SPSS version 21. Descriptive statistics were calculated for continuous variables, while categorical variables were expressed as frequencies and percentages. Stratification by age, gender, and BMI was performed, and post-stratification comparisons were assessed using the chi-square test with a significance level of p < 0.05. Results: The mean age of the enrolled children was 27.4 ± 12.6 months, with the majority in the 13–36-month age group (46.1%). Male children constituted 58.2% of the participants, while females accounted for 41.8%. The mean body mass index was 16.3 ± 2.1 kg/m², the mean hemoglobin level was 10.1 ± 1.2 g/dl, and the mean serum ferritin level was 11.7 ± 4.8 µg/L. Iron deficiency anemia was identified in 79 children (56.0%), whereas 62 children (44.0%) did not meet the diagnostic criteria for IDA. Stratified analysis showed no statistically significant association between IDA and gender (p = 0.72), age group (p = 0.31), or BMI category (p = 0.18). Conclusion: Iron deficiency anemia was present in more than half of the children presenting with breath-holding spells in this tertiary care setting. Routine screening for iron deficiency should therefore be considered in children with breath-holding spells to facilitate early diagnosis and management.